Newer Insights of Relationship between Obesity and Pregnancy Complications- a single Centered Prospective Study (World Journal of Current Medical and Pharmaceutical Research, 2023)
Objective: Obesity is a significant public health concern, and its prevalence among pregnant women has been steadily increasing. Maternal obesity is associated with various adverse pregnancy outcomes, including gestational diabetes, preeclampsia, preterm birth, and macrosomia. However, the relationship between obesity and pregnancy outcomes is complex and can vary depending on factors such as pre-pregnancy weight, gestational age, and comorbidities. This single-centered prospective study aims to investigate the impact of obesity on pregnancy outcomes. By assessing a range of outcomes, including gestational diabetes, preeclampsia, preterm birth, and macrosomia, we seek to enhance our understanding of the risks associated with obesity during pregnancy. Materials and Methods: The study will enroll pregnant women attending the antenatal clinic at a single tertiary care center. Women were categorized into three classes based on Body mass index (BMI): normal (BMI 18.5-24.9 kg/m2); overweight (BMI 25-29.9 kg/m2) and; obese (BMI greater than 30 kg/m2). Demographic data, medical history, and prenatal care details will be collected for each participant. The primary outcomes of interest include the incidence of gestational diabetes, preeclampsia, preterm birth, and macrosomia. Gestational diabetes will be diagnosed using glucose tolerance tests, while preeclampsia will be diagnosed based on blood pressure measurements and proteinuria. Preterm birth will be defined as delivery before 37 weeks of gestation, and macrosomia as birth weight above the 90th percentile for gestational age. Secondary outcomes will include neonatal outcomes such as neonatal intensive care unit (NICU) admission, respiratory distress syndrome, and hypoglycemia. Maternal outcomes, including cesarean section rate and postpartum complications, will also be assessed. Conclusion: This single-centered prospective study aims to examine the impact of obesity on pregnancy outcomes. By elucidating the association between obesity and gestational diabetes, preeclampsia, preterm birth, and macrosomia, this research will contribute to our understanding of the risks associated with maternal obesity. The findings may inform clinical practice and interventions aimed at improving outcomes for obese pregnant women and their infants.